The unraveling of Julia [large type] - Scottoline, Lisa (Grand Central Large Print, 2025)
"Lately, Julia Pritzker is beginning to think she's cursed. She's lost her adoptive parents, then her husband is murdered. When she realizes that her horoscope essentially foretold his death, she begins to spiral. She fears her fate is written in the stars, not held in her own hands. Then a letter arrives out of the blue, informing her that she has inherited a Tuscan villa and vineyard--but her benefactor is a total stranger named Emilia Rossi. Julia has no information about her biological family, so she wonders if Rossi could be a blood relative. Bewildered, she heads to Tuscany for answers. There, Julia is horrified to discover that Rossi was a paranoid recluse with delusions of grandeur, who believed herself to be a descendent of Duchess Caterina Sforza, a legendary Renaissance ruler"--